Tratamento da Bexiga Hiperativa Idiopática com Toxina Botulínica: Resultados da Prática Clínica e Expectativas das Pacientes - Maria Inês Portugal Rodrigues (2020)
Background Overactive bladder (OAB) is a prevalent syndrome affecting 11%-16% of the adult population. When first-line pharmacological therapy is not effective, intradetrusorial injections of Onabotulinumtoxin A (BTX-A) might have an important role in symptoms control. The aim of this study was to access the efficacy and safety of intra-detrusor injections of 100U BTX-A in real clinical practice, among women with idiopathic OAB (iOAB). Methods A retrospective study, based on clinical diaries in 136 iOAB female patients, with or without urinary incontinence, submitted to BTX-A injections, between 2005 and 2018 in a tertiary university hospital. A positive response was considered only when the patient mentioned having great improvement after the injection, otherwise, it was considered negative. Results A positive response was obtained in 90 patients (66%) after the first injection. Women with positive response after the first treatment had 7.5 times more chances to improve with the second (p=0.01). Discontinuation of the therapy after the first injection was not dependent on the presence of incontinence at baseline (p=0.73) nor it was related to age (p=0.6). On univariate analyses, none of the parameters evaluated was useful of predicting successful response, although there was a trend in women who had had a previous midurethral sling (MUS) surgery for stress urinary incontinence (SUI), to have a lower chance of having a positive response after the first injection (p=0.06) Thirty-nine women (29%) had at least one adverse event, urinary tract infection (UTI) and straining to void were the most frequent. Women above 65 y.o. had less risk of developing a UTI (p=0.04). Conclusion In real clinical practice, BTX-A injection is an effective and safe treatment, capable of improving patients' quality of life. Moreover, responding to the first injection seems to predict good clinical outcomes in the second treatment. This procedure can be done with minimal restrictions.